Religious studies specification A - Parry, Lesley; Hayes, Jan; Butler, Sheila (Dynamic learning, 2016)
Cover -- Book title -- Contents -- The study of religions -- 1 CHRISTIANITY -- 1.1 Beliefs and teachings -- Testing your knowledge. -- 1.2 Practices. -- Testing your knowledge. -- Christianity glossary -- 2 ISLAM -- 2.1 Beliefs and teachings -- Testing your knowledge. . -- 2.2 Practices. -- Testing your knowledge. -- Islam Glossary -- 3 JUDAISM -- 3.1 Beliefs and teachings -- Testing your knowledge. -- 3.2 Practices. -- Testing your knowledge. -- Judaism glossary. -- Religious, philosophical and ethical studies -- What does the Specification say about the Themes?